2023
DOI: 10.1155/2023/8258354
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Confers Protection against Diquat-Induced Intestinal Damage with Potential Regulation of Redox Status and Ferroptosis in Broiler Chickens

Abstract: Oxidative stress causes damage to macromolecules, including proteins, DNA, and lipid, and has been recognized as a crucial driver of the onset and progression of several intestinal disorders. Pterostilbene, one of the natural antioxidants, has attracted considerable attention owing to its multiple biological activities. In the present study, we established an oxidative stress model in broiler chickens via injection with diquat to investigate whether pterostilbene could attenuate diquat-induced intestinal damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…With the prohibition of antibiotics in feed, the continuous stimulation by the stressors related to large‐scale intensive breeding increased the disease susceptibility of broilers, which severely affected the metabolism in broilers, particularly lipid metabolism. As a resveratrol analogue, PT has been confirmed to possess more desirable properties, such as intestinal absorption capacity, hepatic stability, bioavailability and biotoxicity, and exhibits diverse biological activities and therapeutic potentials, which exerts protective effects against exogenous factors via multiple pathways on various species (Chen et al, 2020; Chen et al, 2023; Liu et al, 2021; Zhou et al, 2019). However, there is still a lack of literature addressing the protective role of PT as a feed additive on the disorder of lipid metabolism in poultry to date.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With the prohibition of antibiotics in feed, the continuous stimulation by the stressors related to large‐scale intensive breeding increased the disease susceptibility of broilers, which severely affected the metabolism in broilers, particularly lipid metabolism. As a resveratrol analogue, PT has been confirmed to possess more desirable properties, such as intestinal absorption capacity, hepatic stability, bioavailability and biotoxicity, and exhibits diverse biological activities and therapeutic potentials, which exerts protective effects against exogenous factors via multiple pathways on various species (Chen et al, 2020; Chen et al, 2023; Liu et al, 2021; Zhou et al, 2019). However, there is still a lack of literature addressing the protective role of PT as a feed additive on the disorder of lipid metabolism in poultry to date.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that PT exerted protective effects on liver of broilers against oxidative stress by decreasing the content of MDA and increasing the levels of antioxidant enzymes (T‐SOD, CAT, GSH‐Px), while 400 mg/kg PT supplementation was preferable. It has been reported that PT as an antioxidant agent, could directly react with ROS forming stable semiquinone through 4′‐hydroxyl group, to terminate the ROS oxidative chain reaction (Chen et al, 2023). Additionally, like other polyphenols, PT has been shown to exert antioxidant potential by activating the Nrf2 pathway in a variety of species (Chen et al, 2023; Wang, Liu, Liu, et al, 2022; Wang, Liu, Zhou, et al, 2022; Zhang, Chen, Li, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, maintaining intestinal health is crucial for promoting the efficient performance of animal production [19,20]. Some reports found that PTE and resveratrol supplementation in diet improved the structure and function of the intestinal mucosal barrier in animals [21,22]. Zhang et al found that dietary PTE and resveratrol effectively reduced the diamine oxidase (DAO) activity and D-lactate content in the damaged intestine of weaning piglets, with PTE having a more significant effect than resveratrol.…”
Section: Introductionmentioning
confidence: 99%